“Favoured by the Venerable Lord Paśupati” Tracing the Rise of a New Tutelary Deity in Epigraphic Expressions of Power in Early Medieval Nepal - Mirnig, Nina (Indo-Iranian journal, 2013)
The Paśupatināth temple in Kathmandu, dedicated to the deity Śiva Paśupati, is Nepal’s national shrine. The existence of this site and local Śaiva religious activities can be traced back to as early as the fifth century ce, but it was the ruler Aṃśuvarman (fl. 605–621) who first publicly declared his allegiance to the god of the main shrine by styling himself as “favoured by the Venerable Lord Paśupati” in his inscriptions. This allegiance would remain deeply implanted in the religio-political discourse of Nepal thenceforth. Mainly on the basis of the epigraphical record, this article investigates some historical and political processes responsible for shaping the links between Śiva Paśupati as a religious symbol and the ruling elite of Nepal in this early phase, a period in which powerful ministers gradually supplanted the royal elite. Thus, in the wake of Aṃśuvarman’s reign the Paśupatināth shrine had also risen to enough prominence to be included in the list of sacred Śaiva sites in the Indic religious scripture Skandapurāṇa.